1997
DOI: 10.1002/hlca.19970800412
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Enzyme‐Mediated Glycosylation of Natural Polyhydroxy Compounds. Part 1. Galactosylation of stevioside and steviolbioside

Abstract: Bovine ~-1,4-galactosyltransferase is an efficient catalyst for the regioselective transfer of galactose from UPD-galactose, generated in situ with the UDP-glucose/UDP-glucose-4-epimerase system, to the kaurane glycosides stevioside (1) and steviolbioside (Z), affording the corresponding galactosyl derivatives 3 and 4 in high yields. By a combination of 2 D NMR techniques (COSY, TOCSY, ROESY, HMQC, and HMBC), the structure of the products is established as 13-[(P-~-galactopyranosyl-(l -+ 4)-~-~-glucopyranosyI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
(10 reference statements)
0
8
3
Order By: Relevance
“…182 Uridine 5 Similarly, in a regioselective synthesis, the galactosyl derivatives of stevioside and steviolbioside were afforded in good yields (Scheme 113). 185 On the other hand, it is also possible to transform natural steroidal glycosides by enzymatic degradation procedures and natural saponins having terminal b-D-glucopyranose were treated with b-glucosidase, yielding the corresponding hydrolysed compounds (Scheme 114). 186 …”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…182 Uridine 5 Similarly, in a regioselective synthesis, the galactosyl derivatives of stevioside and steviolbioside were afforded in good yields (Scheme 113). 185 On the other hand, it is also possible to transform natural steroidal glycosides by enzymatic degradation procedures and natural saponins having terminal b-D-glucopyranose were treated with b-glucosidase, yielding the corresponding hydrolysed compounds (Scheme 114). 186 …”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…The taste of steviol glycosides strongly depends on the nature and degree of glycosylation [27]. Several approaches have therefore been developed to modify the glycosylation of steviol glycosides [28][29][30][31][32][33][34][35][36][37][38][39][40]. A combination of two different FTases can be used not only to improve the taste of steviol glycosides, but also to functionalize them.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of more than one glucose moiety bearing a free OHÀC(4), the reaction outcome is strongly dependant on the structure of the substrate. For instance, we have shown that it is possible to have the selective galactosylation of only one of the two or three possible glucose acceptors of stevioside and steviolbioside [10], while, in the case of the more simple ginsenoside Rg 1 (2) that contains two glucose moieties, both saccharides were galactosylated, although at different rates [1]. Due to the increased structural complexity of ginsenoside Rb 1 (1), this compound appeared to be a challenging substrate to get more information on the performance of GalT.…”
mentioning
confidence: 99%
“…Part) [1] [10]. Due to the low solubility of 1, 20% DMSO was added because we have demonstrated that this cosolvent is compatible with the activity of this enzyme mixture [11].…”
mentioning
confidence: 99%